Identifying the functional form of operating rules for hydro–photovoltaic hybrid power systems. (15th March 2022) - Gong, Yu; Liu, Pan; Ming, Bo; Feng, Maoyuan; Huang, Kangdi; Wang, Yibo
Abstract: The hybrid operation of multiple renewables offers a promising option for enhancing resource use efficiency in power systems. The power system operation is guided by operating rules with specified functional forms, e.g., linear operating rules. However, the functional form of the operating rules is pre-determined instead of theoretically analyzed in previous research. This study aims to identify the functional form of the operating rules for hydro–photovoltaic hybrid power systems using mathematical derivation. First, a two-stage hybrid operation model is formulated with current and future stages. The future stage divides the uncertain inflow into two ranges according to whether the water spill happens. After that, the optimal operating condition is obtained by maximizing the power generation for the hybrid operation model. Finally, the analytical functional form of the operating rules is derived by approximating the stage-storage relationship and probability distribution functions with polynomials. The case study of Ertan hydro–photovoltaic hybrid power system from China shows that the proposed operating rules increase the average annual power generation from 16.71 to 17.37 billion kWh (3.95%) compared with the standard operating policy. Therefore, the derived functional form of the operating rules could offer guidelines for effectively improving the hydro–photovoltaic hybrid operation. Highlights: Power curtailment is considered in deriving the optimal operating condition. The analytical operating rules increase hybrid system's power generation by 3.95%. Average inflow greatly influences operating rules compared with photovoltaic power.